Understanding Hypertext in the Context of Reading on the Web: Language Learners' Experience - Arif Altun (Arizona State University, 2015)
This paper explores second language readers' understanding of hypertext in the context of reading on the web from a qualitative research paradigm. A total of six undergraduates English as second language (ESL) students voluntarily participated in this study. The results showed that students' understanding varied depending on the presentation of hypertext readings. The findings suggested that students saw hypertext as a valuable bank of information when they were exposed to linear hypertext. When they encountered the non-linear hypertext, they perceived it as a maze and experienced disorientation. It is concluded that neither computer nor text reading skills alone are an adequate basis to start using hypertext technology in language classrooms.